CRITICAL SUCCESS FACTORS OF FIXED-BASE OPERATORS IN THAILAND: ปัจจัยแห่งความสำเร็จของผู้ให้บริการสถานีอำนวยการบินประจำที่ในประเทศไทย - Aumnuaiworachai, Khemmanat; Huangsuwan, Sutit; Sommaneedoung, Sukanya (วารสารบริหารธุรกิจศรีนครินทรวิโรฒ, 2026)
This study aimed to examine and prioritize the critical success factors of fixed-base operators (FBOs) in Thailand, where seven operators currently operate in the market. A mixed-methods approach was employed, comprising interviews with 12 key informants, including seven senior executives or representatives from fixed-base operators and five representatives from the Civil Aviation Authority of Thailand, together with analysis using the Analytic Hierarchy Process (AHP). Data were collected between December 2024 and February 2025. The findings identified eight critical success factors and 12 performance indicators across four perspectives based on the Balanced Scorecard framework. The AHP results indicated that management and strategic management constituted the most important factor (weight = 0.201), followed by service quality (0.176) and safety (0.171). Together, these three factors accounted for 54.8% of the total weight, reflecting the core dimensions of success to which operators should attach particular importance. This study integrated the concepts of Critical Success Factors, Resource-Based View, Balanced Scorecard, and the Analytic Hierarchy Process in the context of the fixed-base operator industry in a developing country. The findings differed from previous studies conducted in developed countries by showing that, in an emerging oligopolistic market, management-related factors were more important than service quality. This finding reflects the need to strengthen internal organizational capabilities before competing on service excellence. The findings provide practical guidance for operators in allocating resources efficiently, for government agencies in formulating targeted industry promotion policies, and for academics in extending research in the context of developing countries.